B-Sure: a randomized pilot trial of an interactive web-based decision support aid versus usual care in average-risk breast cancer patients considering contralateral prophylactic mastectomy - Manne, Sharon L (Transl Behav Med, 2019)
The use of contralateral prophylactic mastectomy (CPM) is increasing among breast cancer patients who are at average or “sporadic” risk for contralateral breast cancer. Because CPM provides no survival benefit for these patients, it is not medically recommended for them. Decision support aids may facilitate more informed, higher quality CPM decision. The purpose of this study was to evaluate the feasibility and acceptability of B-Sure, an online decision support aid to facilitate informed decisions regarding CPM, and to compare the impact of B-Sure in increasing CPM knowledge, reducing decisional conflict, and increasing preparedness to make the CPM decision among breast cancer patients at sporadic risk who are considering CPM. Ninety-three patients with unilateral, nonhereditary breast cancer considering CPM completed a baseline survey, were randomized to receive B-Sure or Usual care, and completed a 4-week follow-up survey assessing decisional conflict, preparedness to make the CPM decision, and CPM knowledge as well as self-efficacy, perceived risk, worry, CPM motivations, and the surgical decision. Study participation was high. B-Sure was viewed by almost 80% of the participants and was evaluated positively. At follow-up, patients assigned to B-Sure reported significantly higher clarity regarding the personal values relevant to the CPM decision and higher knowledge about CPM. B-Sure had smaller effects on other aspects of decisional conflict. B-Sure improved CPM knowledge and reduced decisional conflict. Patients considering CPM may benefit from an online decision support aid, but may be sensitive to approaches that they perceive as biased against CPM.